Enjeux culturels et sociaux de la circulation de la chanson J’attendrai dans les années 1940 - Beaudet, Simon-Pierre; Savoie, Chantal (Mens. Revue d'histoire intellectuelle et culturelle, 2013)
Cette analyse aborde le cas singulier de la circulation de la chanson J’attendrai dans la culture des années 1940, dont l’analyse des variantes permet de cerner les rapports mouvants d’une chanson aux genres chansonniers et musicaux, aux goûts et aux pratiques du public, ainsi qu’à leur ancrage au sein des champs culturels nationaux. Elle permet même, parfois, de sonder les modalités de l’évolution des modèles des rapports sociaux entre les sexes présents dans différentes versions. Ce sont ainsi autant les enjeux artistiques, culturels, sociaux et intimes à l’oeuvre qui guident notre analyse de ce cas de transfert culturel, que le repérage de vecteurs permettant de formuler une équation de la circulation culturelle des chansons à succès.
https://www.researchgate.net/publication/281628540_Les_temps_sociaux
Keywords: 1900-1999; 1930-1939; 1940-1949; 1990-1999; amérique du nord; amériques; approches et analyses; arts; canada; chanson; culture populaire; discipline; histoire et politique; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; thématiques; études littéraires

Decoding Black Women: Policing Practices and Rape Prosecution on the Streets of Philadelphia - Irving, Toni (NWSA Journal, 2008)
Black women are generally displaced as victims of rape. The police response to the sexual assault of black women in general and lower-class black women in particular is illustrative of how sexual ideologies help construct complex social hierarchies that in turn structure rights. How the law currently deals with rape places black women outside of the narrative frames that legitimate entitlement. Rape continues to stand in for, and effectively obscure, other social, political, and economic concerns. Unpublished and often ignored, the rape narrative is a ripe site to supply oppositional interpretations of national experience and transmit some of the structural problems in the criminal justice system. Pulling from over two thousand “real” rape cases of low-income black women ignored and not investigated in Philadelphia between 1995 and 2000, this article reads black female rape narratives as case studies in order to discuss the way personal narratives of rape victims are structured by competing and overwhelming sociolegal narratives that undercut their reception. As the fastest growing prison population, the presence of the law to punish black women stands in stark contrast to the absence of the law to protect them.
Keywords: 1900-1999; 1990-1999; afro-féminisme; amériques; approches et analyses; arts; corps; cours; discipline; droit; droit des femmes* noires; droits des femmes*; féminisme afroaméricain; histoire et politique; intersectionnalité; inégalités; philadelphie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; science politique; science politique et droit; sex2283; sexisme; systèmes d'oppressions; thématiques; viol; violences; états-unis; études littéraires

The post-colonial studies reader - Ashcroft, Bill; Griffiths, Gareth; Tiffin, Helen (Routledge, 1995)
The Post-Colonial Studies Reader is the most comprehensive selection of key texts in post-colonial theory and criticism yet compiled. This collection covers a huge range of topics, featuring nearly ninety of the discipline's most widely read works. The Reader's 90 extracts are designed to introduce the major issues and debates in the field of post-colonial literary studies. This field itself, however, has become so varied that no collection of readings could encompass every voice which is now giving itself the name "post-colonial." The editors, in order to avoid a volume which is simply a critical canon, have selected works representing arguments with which they do not necessarily agree, but rather which above all stimulate discussion, thought and further exploration. Post-colonial "theory" has occurred in all societies into which the imperial force of Europe has intruded, though not always in the official form of theoretical text. Like the description of any other field the term has come to mean many things, but this volume hinges on one incontestable phenomenon: the "historical fact"of colonialism, and the palpable consequences to which this phenomenon gave rise. The topic involves talk about experience of various kinds: migration, slavery, suppression, resistance, representation, difference, race, gender, place, and reaction to the European influence, and about the fundamental experiences of speaking and writing by which all these come into being. In compiling this reader, the editors have sought to stimulate people to ask: "How might a genuinely post-colonial literary enterprise proceed?" The fourteen sections include: Issues and Debates; Universality and Difference; Textual Representation and Resistance; Postmodernism and Post-Colonialism; Nationalism; Hybridity; Ethnicity and Indigenity; Feminism and Post-Colonialism; Language; The Body and Performance; History; Place; Education; and Production and Consumption. Contributors include many of the leading post-colonial theorists and critics–such as Franz Fanon, Chinua Achebe, Gayatri Chakravorty Spivak, Ngugi wa Thiong'o, Homi Bhabba, Derek Walcott, Edward Said, and Trinh T. Minh-ha–in addition to a number of the discourse's newer voices. The Post-Colonial Studies Reader will prove an authoritative compilation, representing an invaluable contribution to the study of post-colonial theory and criticism.
Keywords: 1900-1999; 1990-1999; approches et analyses; cours; discipline; fem1000; féminisme décolonial; histoire et politique; littérature; premier cycle; périodes historiques; thématiques; études culturelles; études littéraires

Le torrent - Hébert, Anne (Beauchemin, 1950)
Un enfant prisonnier de sa mère, au cœur d’un domaine bruissant d’eaux sauvages (Le torrent) ; un instant de tendresse dérisoire, qui change à jamais la vie sage d’une ouvrière-tricoteuse (La robe corail) ; l’exode vécu comme une fête par une petite serveuse, enfin libre au milieu des dangers (Le printemps de Catherine) ; la visite quotidienne d’un homme frustré à sa sœur, qu’il espère chaque jour trouver morte (La maison de l’esplanade)... Si divers que soient les paysages, les milieux, les situations, ces nouvelles d’Anne Hébert sont toutes tendues par une même force : celle de la passion (amour ou haine) qui saisit l’être dans les premiers temps de son existence, qui ne pourra être "dite" parce que la famille, la société ou la solitude refusent cette parole, et qui ne se délivrera d’elle-même que dans la mort — meurtre ou suicide. On retrouvera, à la mesure de ces thèmes, les qualités que "Les chambres de bois" et les "Poèmes" avaient révélées : sens concret de l’instant, vigueur et brièveté de l’écriture, saveur terrienne des images et des mots.
Section: 171 pages
Keywords: 1900-1999; 1990-1999; amériques; arts; canada; cours; discipline; histoire et politique; lit3495; littérature; maternité; premier cycle; périodes historiques; québec; régions géographiques; thématiques; études littéraires